Utilization of Media GELIBO (Gemar Literasi dengan Flipbook) for Fourth Grader at Elementary School - Yusella, Yeni; Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The lack of motivation for students in fourth grader of SDN Dinoyo 3 Malang is the lack of motivation to read, the low understanding of students about the content of reading, and the lack of existing literacy reading books. GELIBO (Gemar Literasi dengan Flipbook) is one of the media to convey information in digital form, where digital information is the impact of technological advances based on the industrial revolution 4.0. This research purpose to analyze the reading and writing literacy ability of elementary school students. The type of research used in this study is qualitative descriptive research. The data were got from the headmaster and teacher by interview, observation, and documentation studies. This research used analysis techniques from Miles, and described Huberman that contained of Data Collection; Data Reduction; Data View; and conclusion drawing/verification. The results showed that the activity of making Mind Mapping is one of the activities that the author wants to do to overcome the lack of students’ interest in reading the existing storybook. The effect of using GELIBO (Gemar Literasi with Flipbook) media can increase students’ interest in learning, it caused of the factors: 1). student intelligence ability, 2). student learning motivation, 3). the influence of playmates, 4). the teacher’s ability, 5). the facilities and infrastructure in the school are sufficient. The condition after the idea, using mind mapping activities written in the media GELIBO (Gemar Literasi dengan Flipbook) can foster students’ interest in reading storybooks in learning at this time. So that this activity can be made a reference to further improve the quality of reading both reading storybooks and reading books reading existing learning materials.